Risankizumab Versus Secukinumab: A Real-World Efficacy and Cost per Responder Comparison in Patients With Psoriasis in Italy - Federico Pirro; Giacomo Caldarola; Nicoletta Bernardini; Maria Grazia Celeste; Annunziata Dattola; Eleonora De Luca; Marco Galluzzo; Domenico Giordano; Chiara Izzi; Giulia Maretti; Lorenzo Marcelli; Roberto Ravasio; et al. (Dermatology Practical & Conceptual)
Introduction: Risankizumab and secukinumab are effective treatment options for patients with moderate to severe psoriasis.